Inherited intragenic PBX1 deletion: Expanding the phenotype. Issue 1 (24th October 2020) - Fitzgerald, Kristi K.; Powell‐Hamilton, Nina; Shillingford, Amanda J.; Robinson, Bradley; Gripp, Karen W.
Abstract: PBX1 encodes the pre‐B cell leukemia homeobox transcription factor, a three amino acid loop extension (TALE) homeodomain transcription factor, which forms nuclear complexes with other TALE class homeodomain proteins that ultimately regulate target genes controlling organ patterning during embryogenesis. Heterozygous de novo pathogenic variants in PBX1 resulting in haploinsufficiency are associated with congenital anomalies of the kidneys and urinary tract, most commonly renal hypoplasia, as well as anomalies involving the external ear, branchial arch, heart, and genitalia, and they cause intellectual disability and developmental delay. Affected individuals described thus far have had de novo variants. Here, we report three related individuals with an inherited pathogenic intragenic PBX1 deletion with variable clinical features typical for this syndrome.